Evaluation of Micronucleus Count in Oral Squamous Cell Carcinoma (OSCC) Newly Diagnosed Patients Compared to Previously Treated Ones: A Cytologic Study - Mohammadi, Marjan; Jalayer Naderi, Noushin; Garajei, Ata; Sajedi, Seyed Masoud (Galen Medical Journal, 2025)
Background: Early detection and monitoring of genomic damages are vital for improving therapeutic outcomes. Quantification of micronuclei in exfoliated buccal mucosa cells has emerged as a reliable biomarker for assessing genomic alterations and cytogenetic damage in precancerous and cancerous conditions. Materials and Methods: This study evaluated exfoliated buccal cells from two groups of OSCC patients: seventeen newly diagnosed individuals who hadn’t yet undergone OSCC treatments and seventeen patients assessed at least six months after treatments. Micronuclei were identified and quantified in the cytology samples, and statistical analyses including the T-test, Mann–Whitney U, Kruskal–Wallis, and Spearman’s correlation tests were applied at a significance threshold of P<0.05 to compare modalities between groups. Results: The newly diagnosed group exhibited a mean micronucleus frequency of 0.028±0.013 per 10³ cell, whereas the treated group demonstrated a significantly lower mean frequency of 0.016±0.020 per 10³ cell (p=0.03). Further stratification of treated patients by intervention type (surgery alone, surgery combined with radiotherapy, and surgery followed by radiotherapy and chemotherapy) yielded mean counts of 0.006±0.003 per 10³ cell, 0.014±0.010 per 10³ cell, and 0.026±0.025 per 10³ cell, respectively. These variations did not reach statistical significance (p=0.29). Conclusion: The findings show that treatment reduces cytogenetic damage, as reflected by diminished micronucleus formation. Consequently, micronucleus assessment in buccal mucosa cells may serve as a noninvasive, cost-effective tool for monitoring therapeutic efficacy and predicting the recovery process in OSCC patients.